Gold-catalyzed highly diastereoselective aynthesis of functionalized 3,4-disubstituted butyrolactams via phosphatyloxy or carbonate double migrations - Yang, Weibo; Zhang, Tuo; Hansmann, Max M.; Pflästerer, Daniel; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2013)
A gold-catalyzed highly diastereoselective synthesis of functionalised 3,4-disubstituted butyrolactams via phosphatyloxy or carbonate double migrations is reported, which is proposed to proceed by a tandem 1,3-phosphatyloxy or carbonate migration and a “long-range” 1,5-phosphatyloxy or carbonate migration, which overall corresponds to a formal 1,6-migration.
Gesehen am 23.07.2021